Impacts of Ocean Wave‐Dependent Momentum Flux on Global Ocean Climate. Issue 20 (22nd October 2020) - Shimura, Tomoya; Hemer, Mark; Lenton, Andrew; Chamberlain, Matthew A.; Monselesan, Didier
Abstract: Accurate knowledge of air‐sea fluxes of momentum, heat, and carbon are central to fully understanding the evolution of the climate system. The role of ocean surface waves has been largely overlooked in global climate models despite the growing body of work elucidating the influence of ocean wave state on air‐sea fluxes. Here we account for the impact of ocean surface waves on global ocean climate using a global ocean model through implementation of wave‐dependent momentum fluxes. Wave‐dependent momentum fluxes improve the simulation of observed ocean heat content (OHC) through increasing the trend in OHC over the last three decades. Specifically, the larger increase in OHC is attributable to increased net heat flux in the Southern Hemisphere (SH). These results highlight the important role of accounting for wave‐dependent momentum transfer in terms of both simulating future climate and understanding changes over the recent historical period. Plain Language Summary: Climate change is one of the main issues of sustainable development. The projection of climate change is important for assessment of impact on our environment, and the global climate model is used for the climate change projection. Accurate knowledge of momentum, heat, and carbon transfer at the atmosphere‐ocean interface, so‐called air‐sea fluxes, is central to fully understanding the evolution of the climate system. Ocean surface waves exist everywhere in the global atmosphere‐ocean interface. Many previous studies found that the air‐sea fluxes are controlled by ocean surface waves. However, the roles of ocean surface waves are ignored in the global climate model. Here we account for the impact of ocean surface waves on global ocean climate. Ocean wave‐dependent fluxes improve the simulation of ocean heat storage through increasing the trend in ocean heat storage over the last three decades to be more in line with observed historical changes. These results highlight the important role of accounting for wave‐dependent air‐sea fluxes in terms of both simulating future climate and understanding changes over the recent historical period. Key Points: Wave‐dependent momentum fluxes are implemented in a global ocean‐sea ice model This results in a significantly improved ability to reproduce observed ocean climate state and variability Accounting for wave‐dependent momentum fluxes significantly improves the simulation of ocean heat content